PENERAPAN PENDEKATAN TPACK YANG DIINTEGRASIKAN DENGAN MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KREATIF MAHASISWA PADA MATA KULIAH PENGEMBANGAN PROFESI GURU - Muskitta, Marike; Tuaputty, Hasan; Latupeirissa, Louvenska (Program Studi Pendidikan Biologi FKIP Unpatti, 2023)
Background: This research aims to improve critical and creative thinking skills in teacher professional development courses through the application of the TPACK approach which is integrated with the Project Based Learning (PjBL) model. Method: This research uses an exploratory research model. Qualitative data was obtained after the pretest, during learning, after the posttest through interviews and questionnaires. Quantitative data was obtained through pretest and posttest data. The research subjects were Biology students at FKIP Pattimura University who offered teacher professional development courses. The research instrument used was a test. Quantitative data analysis uses descriptive statistics and test scores, while qualitative data analysis uses data collection procedures, data reduction, data presentation, and building a conclusion. Results: The results of calculating the implementation of the TPACK approach integrated with the Project Based Learning (PjBL) model to improve students' critical and creative thinking skills in teacher professional development courses show an average value of 89.90 with a significant value of 0.000, which is smaller than 0. 05 (0.000<0.05) so the hypothesis can be accepted. Conclusion: The application of the TPACK approach integrated with the Project Based Learning (PjBL) model is very effective in improving the critical and creative thinking skills of prospective biology teacher students. Keywords: TPACK, PjBL, critical thinking, creative thinking. teacher professional development.